Terapi Bermain Plastisin Terhadap Penurunan Kecemasan Akibat Hospitalisasi Pada Anak Usia Prasekolah (3-6 Tahun) Diruangan Anak RSIA Sitti Khadijah Kota Gorontalo - Sumuri, Megawati; Akifah Sudirman, Andi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The impact of hospitalization and anxiety on children can affect the child's growth and development and hinder the healing process. Another effect experienced by children is rejection of treatment. One effort to overcome anxiety can include play therapy. In this study, to determine whether plasticine play therapy reduces anxiety due to hospitalization in preschool children (3-6 years) in the children's room at RSIA Sitti Khadijah, Gorontalo City. Methods: used in this research was pre-experimental with a one-group pre-post test design approach, the population in this study were children undergoing hospitalization in the children's room of RSIA Sitti Khadijah, Gorontalo City, so the number of samples in this study was 15 people child. Results: Based on the statistical results, the sig or pvalue obtained was 0.008<0.05, which indicates that plasticine play therapy is effective in reducing anxiety due to hospitalization in preschool aged children (3-6 years) in the children's room at RSIA Sitti Khadijah, Gorontalo City. Conclusion: It is hoped that this can provide additional information to health workers at RSIA Sitti Khadijah, Gorontalo City about providing plasticine play therapy which is effective in reducing anxiety due to hospitalization in children.